Imperfect competition, sequential auctions, and emissions trading: An experimental evaluation - Morten Søberg (Statistics Norway, Research Department, 2000)
This paper reports an experiment that studies the behavior of a monopolist on sequential auction markets for tradable permits. Using six sessions in a triple ABA crossover design, we investigate the cost-effectiveness of permit allocations and the division of trade gains on sequential bid, offer, and double auction markets. The main result is that cost-effectiveness and supra-competitive profits accrued by the monopolist are observed on all the three auction markets.
Keywords: L12; Q25; C91; 330; Market power; tradable permits; and experimental economics.